Subordinación y agencia: el personaje principal de la película Juliana - Morales Polar, Martha (2023)
This essay intersectionally analyzes the main character of the film Juliana (1989) in order to highlight the marginal space that frames her and in which she essentially moves, as well as the space where the relations of power and subordination that condition her in the face of the male figure, demanding that he accept submission as a maternal inheritance. It is recalled how race and social class are superimposed on these factors, thus creating simultaneous subordinations. However, it is argued that despite these multiple layers of oppression, Juliana resists and develops an agency that places her in a constant position of questioning, allowing her to challenge the established order.